Poorly differentiated angiosarcoma without vasoformative channels but with focal intracytoplastic vacuoles mimicking liposarcomas - Tadashi Terada, MD, PhD (Elsevier, 2016)
Angiosarcoma (AS) showed diverse morphologies from well formed malignant vasculatures to poorly differentiated tumor with only a few clues of endothelial differentiation. Herein reported are two cases of AS without primitive vasoformative channels (VC). They showed, instead, a very few foci of intracytoplasmic vacuoles (ICV) that mimicked liposarcoma. The two cases were found in 12 cases of AS in computer database. Both are men, 57 and 68 years. One is cutaneous (foot) AS and another is soft tissue (thigh) AS. The largest diameter of cutaneous AS was 5 cm, and that of soft tissue AS 9 cm. The prognosis of both patients was poor; both died of metastases 4 and 6 years after initial presentation. In both cases, hematoxylin and eosin (HE) diagnosis was difficult because there were no VC, and most of the tumors were composed of primitive mesenchymal tissues. In both cases, however, a few very tiny foci consisting of ICV were seen. At first, the author considered them as mucins or fat, and suspected liposarcoma. In fact, they were pseudolipoblasts. Several mucin stains showed no mucins, and fat stains of frozen sections of formalin fixed tissue were negative for fat. Immunohistochemically, the vacuoles were positive for factor VIII-related antigen (F-VIII-RA), Ulex lectin, CD31, CD34, vimentin, p53 and Ki-67 (labeling index = 64% and 75%), but negative for various types of cytokeratins (CK), EMA, CEA, CA19-9, CD45, smooth muscle actins, S100 protein, myoglobin, HMB-45, Melan A, NCAM, and NSE. F-VIII-RA is specific and Ulex lectin and CD31 are relatively specific for endothelium. Therefore, the pathological diagnosis of AS could be made by the combined histologic features (ICV) and Immunohistochemical positivity of F-VIII-RA, Ulex lectin, and CD31. Thus, it appeared that the ICV may be the only clue of poorly differentiated or undifferentiated AS. In such undifferentiated cases, combined observations of meticulous histologic observations (intracytoplasmic lumens and ICV) immunohistochemistry of F-VIII-RA, Ulex lectin, and CD31 may be helpful in the diagnosis of poorly differentiated and undifferentiated AS. Electron microscopic observations were not done in the present study.